ALGORITHM FOR PREVENTION AND TREATMENT OF PRESSURE ULCERS - Franciele Soares Pott; Janyne Dayane Ribas; Otília Beatriz Maciel da Silva; Thaís Sanglard de Souza; Mitzy Tannia Reichembach Danski; Meier Joaquim Marineli (Universidade Federal do Paraná, 2013)
This is a descriptive study, which aimed to describe the development of an algorithm for preventing and treating pressure ulcers, in a University Hospital in Curitiba, Paraná. The elaboration and structuring of the algorithm covered three points: assessment of the nursing, care actions, and therapeutic purpose. It is emphasized that the algorithm is a technology formulated based on scientific evidence for supporting evidence-based practice, which guides the health team's decision-making, allows a broader vision of the entire process, and facilitates the management of the nursing care. It is suggested that studies be undertaken so as to assess the effectiveness of this technology in the light of its application with the nursing team, so as to consider their adherence to the algorithm.